Elevated humidity impairs evaporative heat loss and self-paced exercise performance in the heat - Bright, F. M.; Clark, B.; Jay, O.; Périard, J. D. (Scandinavian Journal of Medicine & Science in Sports, 2025)
This study investigated the effects of absolute humidity on heat dissipation and subsequent thermal, cardiovascular, and performance responses during self-paced exercise in the heat. Twelve trained male cyclists performed a 700-kJ time trial in four different humidity conditions (Low: 1.6 kPa, Moderate: 2.5 kPa, High: 3.5 kPa, and Very high: 4.5 kPa) in 33°C. The gradient in partial water vapor pressure at the saturated skin surface and in air, which determines sweat evaporation, decreased significantly with increasing humidity (Low: 3.53 ± 0.30 kPa, Moderate: 2.74 ± 0.24 kPa, High: 1.99 ± 0.20 kPa, Very high: 1.19 ± 0.16 kPa; p < 0.001). The maximum evaporative capacity of the environment (Emax) also decreased with greater humidity (Low: 309 ± 26 W m-2, Moderate: 240 ± 21 W m-2, High: 175 ± 18 W m-2, Very high: 104 ± 14 W m-2; p < 0.001), as did sweating efficiency (Seff) (Low: 0.50 ± 0.13, Moderate: 0.39 ± 0.10, High: 0.28 ± 0.09, Very high: 0.16 ± 0.04; p = 0.003). Power output was similar between Low (260 ± 33 W) and Moderate humidity (257 ± 27 W; p = 0.999), but lower in Very high (222 ± 37 W) than in all other conditions (p < 0.001) and lower in High (246 ± 31 W) than in the Low and Moderate humidity (p < 0.001). Peak core temperature was higher in Very high (39.49°C ± 0.56°C) than in Low (38.97°C ± 0.44°C; p < 0.001), Moderate (39.04°C ± 0.39°C; p = 0.002) and High humidity (39.12°C ± 0.47°C; p = 0.010). Mean skin temperature was higher with elevated humidity (p < 0.001) and mean heart rate was not significantly different between conditions (p = 0.056). These data indicate that reductions in evaporative potential and efficiency with elevated humidity exacerbate thermal and cardiovascular strain during self-paced cycling in the heat, resulting in marked performance impairments.